IoT-Based Soil Moisture Monitoring and Automatic Irrigation System Using ESP32 and YL-69 Sensors for Oil Palm Seedlings in the Main Nursery - Septia Dwi Pratiwi; Raden Aris Sugianto; Muhammad Akbar Syahbana Pane (Sisfo: Jurnal Ilmiah Sistem Informasi, 2026)
This study developed an Internet of Things (IoT)-based soil moisture monitoring and automatic irrigation system for oil palm seedlings in the main nursery using an ESP32 microcontroller and a YL-69 soil moisture sensor. The proposed system integrates a relay module, a water pump, and the Blynk Cloud platform to provide real-time soil moisture monitoring, threshold-based automatic irrigation, and cloud-based remote monitoring within a single IoT platform. A prototype-based development approach consisting of problem identification, system design, implementation, testing, and evaluation was employed. Experimental evaluation conducted over a four-week period demonstrated that the developed prototype successfully differentiated dry, moist, and wet soil conditions, transmitted soil moisture data to the Blynk dashboard through a Wi-Fi connection in real time, automatically controlled irrigation based on a predefined soil moisture threshold, and maintained an average daily irrigation volume of 498.75 mL. The system also implemented a consecutive-reading confirmation mechanism to improve operational stability by reducing unnecessary relay switching caused by temporary sensor fluctuations. These findings indicate that the proposed system successfully integrates real-time soil moisture monitoring, threshold-based automatic irrigation, and cloud-based remote monitoring into a single IoT platform for supporting automated irrigation management of oil palm seedlings in the main nursery.